Mathematical Creative Thinking Ability using the Discovery Learning Model with the Probing-Prompting technique for Vocational High School Students - Idhata Nurbaiti; Akhmad Jazuli (UM Purwokerto Press, 2025)
The purpose of this study was to determine the mathematical creative thinking ability of Kesatrian Purwokerto High School students on the topic of trigonometry using the Discovery learning model and Probing-Prompting technique. The research design used true experimental design type post test only control design. The research sample was X TJKT 1 class of 37 students and X TJKT 2 class of 36 students and used cluster random sampling technique. Of the two classes taken TJKT 1 class as an experiment, TJKT 2 class as a control.The results showed: 1) There is an effect of Probing Prompting learning model on students' creative thinking skills, 2) There is an influence of the discovery learning model on students' thinking skills. The conclusion of this study shows that the ability to think creatively using the probing prompting technique is better than the class that uses the discovery learning model.